Frequency and Risk Factors of Early Complete Heart Block Post Cardiac Surgery in Children: A Multicenter Prospective Study - Lamiaa Abdelrahman Ibrahim; Mohamed Mosaad Soliman; Asmaa Hassanein Gad Elkarim; Amira Esmat El-Tantawy (Cairo University, Faculty of Medicine, Department of Pediatrics, 2023)
Background: Complete heart block (CHB) remains a foremost complication post cardiac surgery with subsequent medical, social, and financial burden. Aim of work: To evaluate the frequency of early permanent CHB in children and to assess the contributing risk factors among children with congenital heart disease (CHD) who underwent surgical correction. Material and Methods: A prospective descriptive study included 1668 patients post cardiac surgery, who were enrolled from two tertiary centers; Cairo University Children Hospitals and Atfal Misr Insurance Hospital, from February 2019 to February 2020. Medical history, examination, perioperative data as aortic clamp time and cardio bypass times and electrocardiogram were recorded. Results: from a total of 1668 patients, 50 (3%) developed early permanent CHB. Their mean age at the time of the operation was 59.37 ± 41.91months (median:19 months, range: 5-144 months), 62%weremalesand38%females.TheyunderwenttotalsurgicalrepairforFallottetralogyin 25 (50%) patients, ventricular septal defect in 14 (28%), atrial septal defect in 3 (6%) and common atrioventricular canal in 6 (12%). All 50 patients had undergone clamping of the aorta for a mean ± SD of 42.6 ±16.05 min, (median: 42 min, range: 5-105 min) and cardio bypass with a mean ± SD of 65.4±20.34 min, (median:60, range:10-145min). Prolonged aortic clamp (p=0.001) and cardio bypass times (p=0.003) were important risk factors of CHB. Thirty-eight (76%) patients were scheduled for pacemaker implantation, 12 (24%) died from complications of prolonged surgery. Mortality was related to younger age (p=0.027), and prolonged ICU stay (p=0.001). Conclusion: The frequency of CHB post open cardiac surgery was 3%. Early permanent CHB is related to perioperative parameters such as aortic clamp time and cardio bypass time. Mortality in patients with CHB is linked to younger age, and prolonged ICU stay.